Dietrich von Hildebrand, Christian personalist philosopher (Cultura Económica, 2019)
Abelardo Pithod, usual collaborator of our journal, presents a portrait of the work and biography of the personalist philosopher Dietrich von Hildebrand (1889-1977), disciple of the phenomenological philosophers Husserl, Reinach and Scheler. In 1914 he converted to Catholicism, being his permanent ideal of life a deep searching for mankind’s transformation in Christ. The nature and value of human and religious love are two of his work’s most meaningful themes.
Keywords: phenomenological philosophy; psychology; values; Christian authors